Effect of physical vapor deposited bilayer (AlCrN + TiAlN) coating on high-speed steel single point cutting tool. Issue 4 (12th March 2017) - Vannan, R. Ravi Raja Malar; Moorthy, T. V.; Hariharan, P.; Prabhu, P.
ABSTRACT: This paper presents the investigation of hardness, tool weight loss percentage, surface roughness, surface morphology and tool worn-out morphology of high-speed steel (HSS) single point cutting tool and aluminum chromium nitride and titanium aluminum nitride (AlCrN +TiAlN) bilayer coated HSS tool. The two tools with predetermined geometries were analyzed in the same machining conditions at the same center lathe. The results identified that the weight loss percentage of the bilayer coated tool was less when compared with the uncoated tool. Additionally, the hardness of the bilayer coated tool was greater than the uncoated tool. Surface roughness of the bilayer coated tool was lower than the uncoated tool and tool wear was less for the bilayer coated tool when compared to the uncoated tool.